Physiological Workload and Postural Discomfort Among the Farm Women During Vegetable Transplanting (Indian Journal of Extension Education, 2019)
Manual transplanting of vegetable saplings are labour intensive and time consuming operation. During the manual transplanting of saplings of vegetables, farm workers are highly affected by excessive physiological workload and postural discomfort which are the major cause of human drudgery. Pace of work, time spent in various activities, static body position and physiological and mental strain etc. are also the important factors which affect the work capacity of the farm workers. The study was undertaken to assess the physiological workload and postural discomfort among farm workers during conventional method and mechanized method of vegetable sapling transplanting. Physiological parameters i.e. HR, energy expenditure, TCCW and PCW etc. were measured during transplanting operations. The center of gravity method was used to assess the postural discomfort among farm workers. Total 30 farm women were selected for the study. The results revealed that working heart rate (HR work) of the subjects when the vegetable seedling transplanting was performed with conventional method ranged from 122.25 to 154.65 beats/min with a mean value of 135.65 ± 9.54 beats/min. OCR was found to be 1.06 ± 0.38 and 0.54 ± 0.43 l/min, respectively for manual and mechanized method of vegetable transplanting.